Longitudinal multilevel models of the big-fish-little-pond effect on academic self-concept: counterbalancing contrast and reflected-glory effects in Hong Kong schools. - Marsh, H; Kong, C; Hau, K (2000)
Longitudinal multilevel path models (7,997 students, 44 high schools, 4 years) evaluated effects of school-average achievement and perceived school status on academic self-concept in Hong Kong, which has a collectivist culture with a highly achievement-segregated high school system. Consistent with a priori predictions based on the big-fish-little-pond effect (BFLPE), higher school-average achievements led to lower academic self-concepts (contrast effect), whereas higher perceived school status had a counterbalancing positive effect on self-concept (reflected-glory, assimilation effect). The negative BFLPE is the net effect of counterbalancing influences, stronger negative contrast effects, and weaker positive assimilation effects so that controlling perceived school status led to purer--and even more negative--contrast effects. Attending a school where school-average achievement is high simultaneously resulted in a more demanding basis of comparison for one's own accomplishments (the stronger negative contrast effect) and a source of pride (the weaker positive assimilation effect).